ANALISIS KEPASTIAN HUKUM DALAM INVESTASI REKSADANA ONLINE OLEH APERD DIGITAL (Studi Regulasi dan Perlindungan Investor Apabila Terjadi Kegagalan Sistem) - Muhammad Rezalino Saleh Tabalema; Putri Maha Dewi; Fatma Ayu Jati Putri (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the legal protection provided in the implementation of online mutual fund investment services by Digital Mutual Fund Selling Agents (APERD Digital) for investors in the event of system failure or losses caused by technological malfunctions. It also examines the synchronization of regulations governing online mutual fund investment activities to ensure legal certainty for all parties involved. This research employs a normative legal research method using secondary data consisting of primary, secondary, and tertiary legal materials. Data were collected through library research and analyzed using a qualitative approach. The results indicate that the implementation of online mutual fund investment through APERD Digital has expanded public access to investment opportunities while simultaneously creating more complex legal relationships due to the use of electronic systems. Investor protection has been normatively regulated through various legal instruments, including the Capital Market Law, the Electronic Information and Transactions Law, the Consumer Protection Law, the Personal Data Protection Law, and regulations issued by the Financial Services Authority (OJK), which provide both preventive and repressive legal protection. However, this study finds regulatory inconsistencies in the form of overlapping authorities, differences in the regulation of electronic system operators' liabilities, and the absence of explicit provisions governing the liability of APERD Digital for investor losses resulting from system failures. These conditions have the potential to create legal uncertainty, obscure the rights and obligations of the parties involved, and weaken investor protection. Therefore, comprehensive regulatory synchronization is necessary through the harmonization of legal norms, clarification of responsibilities, and strengthening of supervisory and dispute resolution mechanisms in order to establish legal certainty and effective legal protection for investors while supporting the development of a fair and sustainable digital capital market.